Pengaruh Konsentrasi Chemical Agent (Detergen, NaOH) Dan Tekanan Trans-Membran Pada Pencucian Membran Dari Proses Pengolahan Air Gambut Secara Cross Flow - Rahmi Ayuni Fuadi; Syarfi Daud; Maria Peratenta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Peat water is the kind of surface water that which widely available in the swampy area and lowlands that require more treatment so that can beclassified as a clean water and can be drunk. One of the alternative technology that can be used for peat water treating is membrane technology. The first challenge of the membrane technology is fouling. The purpose of this research is to learn the affectivity and efficiency of the cleaner materials likeNaOH and detergent in the regeneration process of ultrafiltration membrane at the peat water filtering operation. This research was done by using ultrafiltration membrane that the peat water as the feed. The used methodwas cross flow system with variations were pressing operation 1 bar and 1,5 bar and concentration of NaOH and detergent 1%, 1,5%, and 2%. The filtering process of peat water carried on for 120 minutes and the each cleaning time was 20 minutes. The highest of cleaning affectivity was reached 21,14% using detergent 2%. The highest of cleaning efficiency based on recovery flux was 84,88% and based on resistance removal was 21,09%.Key words : Cleaning affectivity, cleaning efficiency, peat water, ultrafiltration membrane